PENGARUH MANAJEMEN ASET, PROFITABILITAS, DAN LIKUIDITAS TERHADAP EARNING PER SHARE - Julianti, Kenda; Sahara, Khasanah; Seviasari, Rike (Journal Accounting International Mount Hope, 2023)
Investment activities have now become one way to get additional income or profit from placingfunds in certain companies. Before investing in stocks, investors need to consider the company'sfinancial health by looking at its financial statistics such as the value of the company's earningsper share. This study aims to determine the effect of asset management, profitability, and liquidityon earnings per share in pharmaceutical companies listed on the IDX this year. From a populationof 12 companies, 10 companies were obtained as a population with 3 research periods, namely2019-2021. The analytical methods used in this study are prerequisite analysis tests, multiplelinear regression analysis, and hypothesis tests with SPSS version 26 tools. The independentvariables in this study are asset management (TATO), profitability (ROE), and liquidity (CR). Whilethe dependent variable is earnings per share. The results showed that asset management (TATO)and profitability (ROE) have a positive and significant effect on earnings per share. Meanwhile,liquidity (CR) does not significantly affect earnings per share. Simultaneously, asset management(TATO), p